Information Computing and Applications International Conference, ICICA 2010, Tangshan, China, October 15-18, 2010. Proceedings, Part I - Zhu, Rongbo; Zhang, Yanchun; Liu, Baoxiang; Liu, Chunfeng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the International Conference on Information Computing and Applications, held in Tangshan, China, in October 2010.
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Software engineering; Information theory; Computer software; Computer Science; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Software Engineering; Software Engineering/Programming and Operating Systems; Theory of Computation; Computer Systems Organization and Communication Networks